An analysis of Kansas farm structure, 1973-2007 - Snider, Lindsey K. (Kansas State University, 2008)
This thesis will determine if economies of size are present in production agriculture or the farming sector and if convergence or divergence is occurring. Change in the farming sector was analyzed using five-year moving averages from 1973 to 2007. Six key variables were analyzed; value of farm production, total acres, economic total expense ratio, operating profit margin ratio, asset turnover ratio, and percent of livestock income. Data from the Kansas Farm Management Association were used in this study. To be included in the study, a farm had to have five years of continuous, usable data for a five-year period between 1973 and 2007. Moving five-year averages were calculated for the farms that met this qualification. Data were sorted by value of farm production and broken down by quartiles and deciles. Trend regressions were used to calculate growth rates of the key variables and the difference between the top and bottom quartiles of the variables. Results suggested that acreage per farm is increasing, farms are doing better at covering their total economic costs, profit margin per farm has decreased, farms are utilizing their assets better, and the percent of livestock income per farm has decreased. When regressing the difference between the top and bottom quartiles to determine growth rates, it was evident that the gaps between the top and bottom quartiles of five of the six variables have widened. The differences in the percent of livestock income between farm quartiles and deciles were not significant. Convergence analysis confirmed the results of the trend regressions and suggested that divergence is evident in the Kansas farming sector. Graphical representation supports the findings of this thesis.
Keywords: Farm structure; Economies of size; Kansas; Convergence; Agriculture, General (0473)